PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIFI TIPE THINK TALK WRITE TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI SMA ADABIAH 2 PADANG - VANYA ARIDANTHY (Jurnal Edukasi dan Penelitian Matematika, 2021)
One goal ofilearning mathematics understanding mathematical  concepts. But in reality  in Padang Adabiah 2 High School, this ability is still not optimal. Learning strategies have not been able to improve students' understanding oficoncepts. Ifuthis ability is low, it will affect other mathematical abilities. The research objective is to analyze the increase in understanding of the concepts ofustudents who learn with Think Talk Write learning models and describe whether understanding the concepts ofustudents who learn with Think Talk Write learning models is better than understanding the concepts ofxstudents who learn with  direct  learning  models  in  class XI  MIA SMA Adabiah 2 Padang Academic Year 2019/2020. Keywords — Think Talk Write, Mathematical concepts